Quantification and characterization of enteric methane production by C isotopic composition (delta 13C) in sheep grazing Brachiaria brizantha cv Xaraés and Tithonia diversifolia - Krüger, Ana Maria (2023)
Grazing systems are a pillar for the development of society in the entire world, mostly by supporting the production of grazing ruminants, one the most important and traditional economical activities of humanity. In a moment when there is a world-wide debate and scrutiny on topics such as climate change and increasing human population, there is a need of increasing food production, especially animal-derived protein, causing as minimum as possible of environmental impacts. Well managed grazing systems can be considered as an opportunity to overcome such problems. Silvo-pastoral systems, where grass forages are intercropped with trees and shrubs are one of the alternatives for grazing management that has potential to provide adequate animal productive performance while reducing impacts of the production system. Tithonia diversifolia (Hemsl.) A. Gray is a shrub species that has been pointed out as capable of reducing greenhouse gas emissions in production systems even though it has not been widely studied by the scientific community. This thesis presents one literature review that aimed to provide an overview and current state of knowledge about the potential of silvo-pastoral systems, especially those using T. diversifolia, to provide sustainable intensification of animal production and two research mansucripts: one in vitro batch culture trial which was done using increasing levels of T. diversifolia on tropical grass-based substrates and the other one was an in vivo methane (CH4) measurement assay using Santa Inês lambs grazing on a Brachiaria brizantha cv Xaraés pasture intercropped with T. diversifolia, where data on feed digestibility, feed intake, CH4 production, C isotopic composition of CH4 and ruminal fermentation parameters were collected. Even though feed intake, feed digestibility and CH4 production were not affected by the presence of T. diversifolia in the diet ( P > 0.05) in our in vivo assay, in vitro CH4 production was reduced and results on isotopic composition of gases and fermentation residues of our in vitro trial, as well as fermentative parameters of both experiments provided evidence that the inclusion of this plant may be beneficial for tropical production systems, potentially allowing improved animal performance coupled to reduced intensity of CH4 emissions.